Vibration analysis, instruments, and signal processing - Sinha, Jyoti Kumar (Boca Raton : CRC Press, Taylor & Francis Group, CRC Press is an imprint of the Taylor & Francis Group, an informa business, 2015)
'Preface Over the past four decades, the technology in vibration instrumentation and measurements, signal processing, and analytical simulation using finite element (FE) methods has advanced significantly. There are several dedicated books that have recorded these advancements. However, it has been consistently observed that several persons (students, researchers, designers, and maintenance personnel in industry) involved in, say vibration- related works or research, do not fully comprehend the interrelation between theory and experiments. These individuals can be grouped as (1) good in vibration data collection but may not be aware of the applicable basic theory, and vice versa, (2) good in signal processing but may not know the basics of either the theory or vibration data collection and measurement procedures, and (3) involved in dynamic qualifications (FE analysis and modal testing) using standard commercially available software without knowing much about the basic principles and methods. It is imperative that persons involved in vibration-based analysis have at least a basic understanding of the different processes so that they can more effectively solve vibration-related problems. This book aims to communicate the fundamental principles of all three facets of vibration-based analysis (i.e., instruments and measurement, signal processing, and theoretical analysis) in a simplified tutorial manner, which is not readily available in literature. The unique content of this book will therefore be very useful for a diverse audience who are interested in vibration analysis. The target audience includes students (all levels), researchers, and engineers (involved in vibration-based condition monitoring)'--
Includes bibliographical references and index.
Keywords: Vibration -- Measurement; Damping (Mechanics).